2010
DOI: 10.1007/s10143-010-0258-5
|View full text |Cite
|
Sign up to set email alerts
|

2-Octyl-cyanoacrylate for wound closure in cervical and lumbar spinal surgery

Abstract: It is claimed that wound closure with 2-octyl-cyanoacrylate has the advantages that band-aids are not needed in the postoperative period, that the wound can get in contact with water and that removal of stitches is not required. This would substantially enhance patient comfort, especially in times of reduced in-hospital stays. Postoperative wound infection is a well-known complication in spinal surgery. The reported infection rates range between 0% and 12.7%. The question arises if the advantages of wound clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 37 publications
(68 reference statements)
0
29
0
Order By: Relevance
“…Of the 34 articles that underwent full-text review, 12 [22][23][24][25][26][27][28][29][30][31][32][33] met eligibility criteria for inclusion in the meta-analysis and 22 were excluded. The most common reasons for exclusion of the 22 studies were: criteria for the diagnosis of SSI not reported and/or CDC/NNIS criteria not applied [34][35][36][37][38][39][40][41][42][43][44][45][46][47], non-scalar definitions of obesity used [47][48][49], risk estimates of the association between obesity/BMI and SSI not reported or raw data not provided to calculate risks [44,47,[50][51][52][53], and analyses restricted to deep wound infections [54,55].…”
Section: Literature Search and Systematic Review Resultsmentioning
confidence: 99%
“…Of the 34 articles that underwent full-text review, 12 [22][23][24][25][26][27][28][29][30][31][32][33] met eligibility criteria for inclusion in the meta-analysis and 22 were excluded. The most common reasons for exclusion of the 22 studies were: criteria for the diagnosis of SSI not reported and/or CDC/NNIS criteria not applied [34][35][36][37][38][39][40][41][42][43][44][45][46][47], non-scalar definitions of obesity used [47][48][49], risk estimates of the association between obesity/BMI and SSI not reported or raw data not provided to calculate risks [44,47,[50][51][52][53], and analyses restricted to deep wound infections [54,55].…”
Section: Literature Search and Systematic Review Resultsmentioning
confidence: 99%
“…To identify the rate of infection associated with spinal surgery after wound closure with octyl-2-cyanoacrylate, a study was performed in a total of 235 patients with one-or two-level surgery of the cervical or lumbar spine [ 59 ] . Skin closure was performed with octyl-2-cyanoacrylate after anterior cervical ( n = 100) and dorsal lumbar ( n = 135) spinal surgery.…”
Section: Cyanoacrylatesmentioning
confidence: 99%
“…2‐octyl cyanoacrylate (Dermabond, Ethicon Inc., Somerville, NJ) is an FDA‐approved topical medical adhesive that has been shown to have excellent adhesive properties and low reactivity in vivo . It has been studied in a variety of ophthalmologic, neurosurgical, and cardiothoracic procedures, among others. Early reports of use of cyanoacrylate derivatives in the middle ear to augment ossiculoplasty using hydroxyapatite prostheses exist; however, there are no detailed reports of extrusion rates using this technique in the long term with use of titanium prostheses.…”
Section: Introductionmentioning
confidence: 99%